Merger Bank Bermasalah di Indonesia - Indrawati, Titik (Bina Nusantara University, 2001)
The basic of problem for direction and senior manager bank is how to maximalize the value of share owner. It focus on how to make value by merger, how to get the value of bank target, and how to consider the nonfinancial influence the value by merger. The objective of the research wrap up the traveling’s merger and acquisition phenomenon in Indonesia. That objective are more focused on how merger can increase value, how to decide Bank’s value and the non financial parameter that can affact the sucsess of the merger comp. It’s concluded that Indonesian society see Bank merger as a final action to save a Bank from Bankcoruptcy. In negotiating the merger agreement, buyer and seller must consider the financial & non financial parameters.